Metabolic Activation of PCBs to Carcinogens in Vivo – A Review - Ludewig, Gabriele (2008)
Many higher-chlorinated biphenyls, persistent and predominant in foods, are active as promoters in hepatocarcinogenesis. Lower-chlorinated biphenyls, predominating in indoor and outdoor air, are more readily metabolized and therefore shorter lived, ‘episodic’ contaminants. Thus inhalation of such lower chlorinated biphenyls may expose humans to reactive, possibly genotoxic/carcinogenic intermediates. Lower chlorinated biphenyls may be metabolized via arene-oxides to mono- and dihydroxylated intermediates and further to (semi)quinones, highly reactive intermediates. Covalently bound lower chlorinated biphenyls have been detected in rodent tissues in vivo. We recently showed using the modified Solt-Farber foci assay that several mono- to tetrachlorinated biphenyls have initiating activity in the livers of rats. In a follow-up study of PCB3 (4-chlorobiphenyl) metabolites only one monohydroxy- and one quinoid- metabolite showed initiating activity, indicating that the metabolic activation of PCB3 proceeds via hydroxylation and oxidation to the 3,4-quinone, the ultimate carcinogen. Since cancer initiation is based on genotoxic event(s), we hypothesized that PCB3 and/or its metabolite(s) are mutagenic in rat liver in vivo. To investigate this, BigBlue® rats, transgenic for the lacI reporter gene, were exposed to PCB3 and 4-hydroxy-PCB3 (4-HO-PCB3). In male rats the mutant frequency (MF) of lac I in the liver was significantly elevated and the mutation spectrum differed significantly from the control. 4-HO-PCB3 caused a non-significant (p = 0.115) doubling of the MF compared to the control. These studies prove that lower halogenated biphenyls may be metabolically activated in vivo to genotoxic and initiating intermediates.